2015
DOI: 10.1016/j.marpetgeo.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish and steady focussed flows through fine-grained sediments: The methane-derived cylindrical concretions of the Tertiary Piedmont Basin (NW Italy)

Abstract: a b s t r a c tIn the Cenozoic succession of the Tertiary Piedmont Basin (NW Italy) a wide array of methane-derived carbonate rocks including both seafloor and sub-seafloor products have been reported in the last decades. The most intriguing features are cylindrical concretions, more than 1 m long and around 10 cm across, that were found within fine-grained sediments of Messinian age in their original stratigraphic position, crossing the bedding planes at high angles. These concretions result from cementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The pioneering work of Jenkins (1930) points to a Paleogene oil migration from the older Moreno Shale to the Kreyenhagen Based on stratigraphic relationships and stable isotope compositions of authigenic carbonates and clastic dikes, Minisini & Schwartz (2007) demonstrated the contemporaneity between these structures and conclude that the dikes controlled the distribution of the seeps. Cavagna et al (2015) and others, reported methanederived carbonate rocks, including both seafloor and sub-seafloor products in the Cenozoic succession of the Piedmont Basin of NW Italy. These authors argue that cylindrical concretions formed just below the seafloor are the result of carbonate precipitation around fluid conduits and record a long period of stable and slow methane seepage.…”
Section: The Methane Seepage In the Serra Alta Epeiric Seamentioning
confidence: 92%
See 4 more Smart Citations
“…The pioneering work of Jenkins (1930) points to a Paleogene oil migration from the older Moreno Shale to the Kreyenhagen Based on stratigraphic relationships and stable isotope compositions of authigenic carbonates and clastic dikes, Minisini & Schwartz (2007) demonstrated the contemporaneity between these structures and conclude that the dikes controlled the distribution of the seeps. Cavagna et al (2015) and others, reported methanederived carbonate rocks, including both seafloor and sub-seafloor products in the Cenozoic succession of the Piedmont Basin of NW Italy. These authors argue that cylindrical concretions formed just below the seafloor are the result of carbonate precipitation around fluid conduits and record a long period of stable and slow methane seepage.…”
Section: The Methane Seepage In the Serra Alta Epeiric Seamentioning
confidence: 92%
“…However, several studies on Phanerozoic seep deposits revealed methane-derived carbonates with a wide range of 13 C values, varying between -30 to +24‰ (see Kauffmann et al 1996, Martens et al 1999, Stakes et al 1999, Greinert et al 2001, Peckmann et al 2002, Reitner et al 2005, Wirsig et al 2012, Cavagna et al 2015, Lash et al 2015. Thus, a plausible methane source in the Irati Formation is compatible with the modestly 13 C-depleted carbonate cements from the Serra Alta concretions and clastic dikes.…”
Section: The Birth and Growth Of The Serra Alta Concretionsmentioning
confidence: 97%
See 3 more Smart Citations